Can the Pope Change Tradition? On Tradition as a Principle of Progress in the Light of Thomas Aquinas’ Theology - Piotr Roszak (Wrocławski Przegląd Teologiczny)
The article analyses the Thomistic understanding of Tradition in the context of the contemporary theological discussion on the extent of changes proposed by recent papal texts, which for one group of theologians is a change of Tradition, and for another a faithful development of it. By recalling the 19th-century understanding of “developing” Tradition forged on the dispute with modernism by Newman, Möhler or Blondel, and juxtaposing it with a Thomistic approach, a conviction is shown that fidelity demands the theologian to develop what is conveyed in the Revelation. Contemporary debates, however, reveal old theological problems, including ultramontanism, which is voiced when the primacy of the Bishop of Rome is reduced to guarding formulas, rather than receiving and illuminating the current problems with the light of Revelation. On the base of the biblical commentaries of St Thomas Aquinas to the Letters of St Paul, the vision of the exercising primacy of the Bishop of Rome will be analysed.